2020
DOI: 10.4025/actasciagron.v43i1.48732
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the harvest time of sugar apples (Annona squamosa L.) in function of carpel interspace

Abstract: Sugar apples have attracted attention in recent years due to their medicinal and nutritional properties. However, the shelf life of sugar apples is one of the most concerning problems owing to their perishability. This work aimed to determine the ideal harvest time for sugar apple fruits in relation to different classes of carpel interspaces. Therefore, fruits were classified into three stages according to the carpel interspace: stage 1 (0.0 - 2.0 mm); stage 2 (2.1 - 3.0 mm); and stage 3 (3.0 - 4.0 mm). After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…The titratable acidity is directly involved with the organoleptic quality of the fruits, influencing its taste and odor, being therefore, a key characteristic that defines fruit quality. Sugar apple cultivars had titratable acidity values similar to those observed in the literature (Moura et al, 2021) but higher than those observed by Pereira et al 2014b, averages of 0.16 g of citric acid 100 g -1 pulp. The low titratable acidity presented in the fruits of sugar-apple cultivars must have occurred due to their rapid maturation, not producing enough organic acids to increase the titratable acidity.…”
Section: Physical and Chemical Characteristicssupporting
confidence: 79%
See 3 more Smart Citations
“…The titratable acidity is directly involved with the organoleptic quality of the fruits, influencing its taste and odor, being therefore, a key characteristic that defines fruit quality. Sugar apple cultivars had titratable acidity values similar to those observed in the literature (Moura et al, 2021) but higher than those observed by Pereira et al 2014b, averages of 0.16 g of citric acid 100 g -1 pulp. The low titratable acidity presented in the fruits of sugar-apple cultivars must have occurred due to their rapid maturation, not producing enough organic acids to increase the titratable acidity.…”
Section: Physical and Chemical Characteristicssupporting
confidence: 79%
“…Both sugar-apples and atemoyas have excellent physicochemical qualities, with changes in chemical composition during fruit ripening (Moura et al, 2021(Moura et al, , 2019bSantos et al, 2016), which makes their taste and aroma more pleasant. The value of annona varies according to the internal and external quality of the fruits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean fruit mass was 638.73 g, peel mass was 282.14 g, and seed mass was 39.30 g, with a mean of 90 seeds. Compared with other sugar apples, 'LeahReese' is generally larger (Crane et al, 2016;Moura et al, 2019Moura et al, , 2021Neto et al, 2010;Pinto et al, 2005;Silva et al, 2007). The fruit has an mean of 50.43% pulp, 25.48 Brix, a pH of 5.01, an acidity of 0.228 g citric acid/40 g of pulp, and a Brix-to-acid ratio of 119.04 (Table 1).…”
Section: Descriptionmentioning
confidence: 99%